CORRELATION AMONG THREE NON-INVASIVE METHODS (APRI, FIB-4 AND TRANSIENT ELASTOGRAPHY) TO EVALUATE LIVER FUNCTION AND STIFFNESS IN PATIENTS WITH VIRAL HEPATITIS C OR SCHISTOSOMIASIS MANSONI - Antonio de Jesus Nascimento, Marco; Palomares Filho, Gilmar; Lima Andrade, Marcel; Augusto de Vasconcelos Ouro Reis, Andre; M. Rocha Baiao, Kennia; Virgínia Silva Bezerra do Nascimento, Tereza; Soares Pacheco, Mauricio (Revista de Patologia Tropical / Journal of Tropical Pathology, 2018)
Both chronic viral hepatitis and schistosomiasis are potentially serious causes of liver fibrosis. Several studies suggest, however, that hepatic fibrosis may be reversible, which highlights the importance, not only of early diagnosis, but, above all, observing this while monitoring the disease. This study aimed to evaluate the correlation between three non-invasive methods for classification of hepatic fibrosis in patients with viral hepatitis or schistosomiasis. The sample consisted of 45 patients with chronic hepatitis with HCV and 17 with schistosomiasis. Medical records were analyzed for data collection related to sex, body mass index (BMI) and laboratory testing for biochemical markers. The evaluation was carried out by means of the following hepatic diagnostic methods: APRI, FIB-4 and Transient Elastography (Fibroscan), and the subsequent correlation analysis by Spearman test (r). There was a predominance of males among patients with HCV (64.4%). HCV patients also presented the highest average age (54.8 years) and high levels of AST and ALT. Positive correlation was noted between APRI and FIB-4 results in patients of both groups; positive correlation between APRI and Transient Elastography in patients with HCV; and positive correlation between FIB-4 and Elastography in patients with HCV or schistosomiasis. Our data suggest that the non-invasive methods for diagnosis and monitoring of hepatic fibrosis present a high degree of acceptance, especially in patients with HCV.